A infância e o pedestrianismo: um estudo exploratório da percepção de crianças sobre indicadores de caminhabilidade - Ryane Moreira Barros (2021)
Urban mobility has become a challenge in most cities around the world. This challenge is strongly related to the unequal division of urban space, since, historically, individual motorized transport has been privileged in comparison to the others, not being considered equally, balanced and fair. Although the displacements on foot are quite expressive in the cities, it is necessary that they gain more visibility, since this is quite democratic and can assist in the promotion of health and well-being. In this context, the concept of walkability seeks to understand which aspects may be favorable to walking, which may or may not be based on the perception of pedestrians. Thus, through this, it can seek to understand what is actually necessary for the urban space to be more favorable to pedestrian movements. In order for the circulation space to adequately serve pedestrians, it is essential to identify and understand the needs of different groups of pedestrians, such as children, a very vulnerable stratum in the dispute for urban space. In this sense, it is important that they are considered during the conception of the urban space, either because of its physical and cognitive development, its great involvement in traffic accidents and for the streets to stop being a prohibited space for them, as in many cases occur. Therefore, it is desirable for children to be included in the process of (re)planning pedestrian circulation spaces, as streets that meet children's desires and needs are likely to serve other pedestrians. Therefore, the objective of this work is to propose a walkability index according to the perception of children, aged between 9 and 12 years old, who live in Belo Horizonte. In order to be able to select the indicators that would compose the walkability index now proposed, a questionnaire was developed and applied using the Likert Scale to identify the children's perception about the relevance of each one of them in their usual displacements. In a second step, the walkability conditions were determined in a school area in Belo Horizonte, based on the application of the developed index, making it possible to verify any weaknesses in this spatiality. The index proved to be easy to apply and very useful in guiding which measures are priority so that a given area can be re-qualified in order to be more child friendly.